Analysis of Cerebral Adherence to Heart Failure Cases in Melati 2B Ward at Dr. Soekardjo Regional General Hospital Tasikmalaya - Cindy Putri Andriyani; Asep Kuswandi; Dewi Aryanti (Universitas Tribhuwana Tunggadewi, 2026)
Heart disease remains a leading cause of global mortality, closely linked to modifiable unhealthy lifestyles. The Indonesian Ministry of Health introduced the CERDIK program as a preventive strategy, encompassing routine health checks, smoking cessation, regular physical activity, balanced diet, adequate rest, and stress management. However, the incidence of heart failure remains high, suggesting inconsistent adherence. This study aims to analyze the risk factors for heart failure based on the CERDIK behavioral approach in Tasikmalaya. A non-experimental quantitative case–control study was conducted involving 60 respondents (30 cases and 30 controls) at RSUD Dr. Soekardjo. Data were analyzed using Chi-Square and Fisher’s Exact Test to determine Odds Ratios (OR). The results revealed that regular physical activity (p 0.001; OR 0.11) and a balanced diet (p = 0.03; OR 0.04) were significantly associated with a lower risk of heart failure. Routine health checks (p 0.001) and adequate rest (p 0.001) also showed strong protective associations. Conversely, stress management did not show a statistically significant association (p = 0.123), likely due to high adherence across both groups. It is concluded that consistent implementation of CERDIK behaviors, particularly physical activity and dietary management, is critical in preventing the progression of cardiovascular disease into heart failure. Healthcare providers must intensify education and monitoring of these specific behaviors in high-risk populations.